2003
DOI: 10.1590/s0066-782x2003000500001
|View full text |Cite
|
Sign up to set email alerts
|

Regional myocardial function in healthy adults: assessment through tissue Doppler echocardiography

Abstract: OBJECTIVE: To characterize left ventricular regional myocardial function through tissue Doppler echocardiography in healthy adults and to assess the influence of aging in this function. METHODS: In 45 healthy volunteers divided in two groups (< 45 and > 45 years old) we assessed longitudinal and radial regional function (velocities, times intervals and velocity-time integrals). Data were compared in each group and between groups. RESULTS: Systolic function: a) longitudinal: higher velocities and integrals in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…This may not be the case, however, when there is regional disease in the basal myocardium. Cardim et al [ 4 ], however, found that tissue Doppler velocities were higher in the lateral and inferior basal segments than in the septal and lateral segments for both systolic and diastolic function. The systolic and diastolic velocities in our study were higher than those reported in [ 4 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may not be the case, however, when there is regional disease in the basal myocardium. Cardim et al [ 4 ], however, found that tissue Doppler velocities were higher in the lateral and inferior basal segments than in the septal and lateral segments for both systolic and diastolic function. The systolic and diastolic velocities in our study were higher than those reported in [ 4 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardim et al [ 4 ], however, found that tissue Doppler velocities were higher in the lateral and inferior basal segments than in the septal and lateral segments for both systolic and diastolic function. The systolic and diastolic velocities in our study were higher than those reported in [ 4 6 ]. This could be due to the younger age of our cohort, and TDI values have been reported to decrease with age [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation